Water saturation effect on the tensile strength of rocks - Loh, Zhonglie. (2011)
In underground cavern construction, rock is saturated to varying degrees due to the presence of ground water. This study aims to investigate the role of the degree of water saturation on the tensile strength of rocks.Three groups of specimens were tested. The first group of specimens was labelled “dry”, which was obtained by placing the specimens in the oven. The second and third groups of specimens were labelled “wet” and “saturated”, which were obtained by saturating the rocks to simulate wet condition onsite and full water saturation respectively. Siltstones with both transverse and longitudinal beddings were tested in this experiment.Brazilian test results showed that the water saturation effect has an adverse impact on the hydromechanical properties of rock. The tensile stress and Young‟s modulus of the rock decreased significantly by up to 22.7% and 13.3% respectively when the rocks were cured under saturated conditions.